FUNGSI DAN MOTIF TOKOH RAKSASA DALAM CERITA ANAK DER ROSTIGE ROBERT UND ELF UNGEHEUERLICHE UNGEHEUER KARYA THILO PETRY LASSAK - APRILIA DEWI, RISKA (UNIVERSITAS NEGERI SURABAYA, 2017)
There are five genres in children’s literature; fictions, non-fictions, poems, folk literatures, and comics (Nurgiyantoro, 2016:30). In addition, Fiction is divided into two categories; novel and short story. Children’s story is one of the forms in the novel which contains plentiful characters. Moreover, the characters have important roles. The characters’ action is needed in order to relieve the conflict within the story. Therefore, the problem statements in this study are (1) what is the role of the giant in Der Rostige Robert und elf ungeheuerliche Ungeheuer by Thilo Petry Lassak, and (2) what is the rationale of Der Rostige Robert und elf ungeheuerliche Ungeheue by Thilo Petry Lassak. This study is aimed to (1) describe the role of the giant in Der Rostige Robert und elf ungeheuerliche Ungeheue by Thilo Petry Lassak, AND (2) to describe the rationale of Der Rostige Robert und elf ungeheuerliche Ungeheuer by Thilo Petry Lassak. The theory used in this study is called as Strukturalisme Propp. According to Propp (1968:25), there are 31 categories of purpose. Besides, there are rationales that underline the purposes. Additionally, this study adopted qualitative descriptive research design. Source of the data was collected from a book entitled Der Rostige Robert und elf ungeheuerliche Ungeheuer by Thilo Petry Lassak. The result of this study showed that the book contains 17 purposes. They are information transfer (ζ), donor (D), fulfilled deviancy (K), amorality (A), swindle (η), prohibition (γ), punishment (U), marks (J), casuistry(θ), medium (B), departure (↑), marriage (W), review (ε), combat (H), triumph (I), seeker (Pr), and manifestation (T). Correspondingly, 8 rationales are found; rationale of deviancy, rationale of amorality, rationale of acceptance sense, rationale of avarice, rationale of amorality , rationale of conquest, rationale of partnership,  rationale of amorality. The framework of the story obtained its own plot and forms a small story based on 17 purposes and 8 rationales. Keywords: role, rationale, giant.